KAJIAN WACANA POLITIK DAN EKONOMI DI KOLOM HARIAN UMUM REPUBLIKA PERIODE JUNI-DESEMBER 2021 - Rahmat Banu Widodo; Fadli Muhamad, Lili (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2024)
The purpose of this study is to analyze and describe the content and meaning of political and economic opinions in the Rubrik's Column of Republika Daily Opinion for the period June – December 2021, the data analyzed are 6 Republika daily opinions. Based on the analysis carried out by the researcher, the results of his research in the general opinion column of the Republika daily for the period June – December 2021 are in line with the critical discourse analysis of Teun AVan Dijk's approach. In the opinion column, the researcher found the results of Van Dijk's version of the three-dimensional AWK analysis, namely macro/thematic structure, Super Structure/ Schematic Analysis and microstructure. Keywords: Discourse Analysis, Economic And Politic, General Opinion HU Republika